Senam Hipertensi menurunkan Tekanan Darah Lansia di Panti Sosial Tresna Werdha Budi Mulia 3 - Achmad Marsaidi Primadi; Budi Mulyadi (Sagamedia Indo Press, 2021)
Introduction: Throughout the world of hypertension is a serious problem, besides because of its high prevalence and cinderung increases in the future, with increasing age it is more at risk of increasing the blood pressure of an elderly person who has reached the age of> 60 years slowly functionally weakened then continued age is susceptible to diseases such as hypertension. Regular movement exercises are important for the elderly so that blood flow returns smoothly and increases oxygen supply. Objective: The purpose of this study was to determine the effect of hypnosis exercise on elderly blood pressure. Method: Methods used in this study is quasi-experiment (onegroup pre-test and post-test) on 16 respondents with paired sample analysis t test. Result: The results showed that there was an effect of hypertension exercise on blood pressure in the elderly (p value = 0,000). Gymnastics can be applied as one of the programs to control elderly blood pressure. Conclusion: hypertension gymnastics is proven to lower blood pressure in the elderly so that this intervention can be used as a supporting therapy in the management of hypertensive patients